Noise orders : jazz, improvisation, and architecture - Brown, David, 1965- (University of Minnesota Press, 2006)
In Noise Orders, David Brown locates jazz music within the broad aesthetic, political, and theoretical upheavals of our time, asserting that modern architecture can be strongly influenced by jazz improvisation. Comparing artists and architects with individuals and groups in jazz-including Piet Mondrian and boogie-woogie, John Cage and Rahsaan Roland Kirk-Brown examines how jazz can provide insight on how to develop dynamic metropolitan environments.